Ta có:
`f(x) = 5x^4 + 5x^3 - x - 1`
`g(x) = x^3(x-1) + 2(x^2 +2)`
`= x^4 - x^3 + 2x^2 + 4`
`h(x) = 4x^3(x-1) - ( x+3)`
`= 4x^4 - 4x^3 - x - 3`
a)
`f(x) + g( x) - h(x) = 5x^4 + 5x^3 - x - 1 + x^4 - x^3 + 2x^2 + 4 - 4x^4 + 4x^3 + x + 3`
`= ( 5x^4 + x^4 - 4x^4) + (5x^3 - x^3 + 4x^3) + 2x^2 + (x - x) + (4 + 3 - 1)`
`= 2x^4 + 8x^3 + 2x^2 + 6`
b)
`p(x) = 5x^4 + 5x^3 - x - 1 - x^4 + x^3 - 2x^2 - 4 + 4x^4 - 4x^3 - x - 3`
`= (5x^4 - x^4 + 4x^4) + (5x^3 + x^3 - 4x^3) - 2x^2 - (x+x) - (1+4+3)`
`= 8x^4 + 2x^3 - 2x^2 - 2x - 8`
`p(2-2) = p(0) = 8. 0^4 + 2 . 0^3 - 2 . 0^2 - 2.0 - 8`
`= 8.0+2.0-2.0-2.0 - 8`
`= 0 - 8`
`= -8`
(Chúc bạn học tốt)